Evaluation of the prehospital diagnostic accuracy of a novel point-of-care test for NT-proBNP, D-dimer and H-FABP and large-vessel occlusion risk assessment (LVOCheck-EVA): a protocol for a multicenter prospective observational study in patients suspected of having a stroke - Röhrs, Kian; Kaffes, Maximilian; Bondi, Fulvio; Zuber, Martina; Kübler-Weller, Dorothee; Haacke, Lisa; Röhle, Robert; Sprünken, Erin Dirk; Schwabauer, Eugen; Wendt, Matthias; de Jesus Gil, Carmen; Sanchez, Jean-Charles; et al. (Frontiers in Neurology, 2025)
IntroductionAcute ischemic stroke (AIS) is a leading cause of permanent disability in adults and one of the most time-sensitive emergencies in modern medicine. Rapid diagnosis and initiation of thrombolytic therapy, as well as immediate access to mechanical thrombectomy for patients with large-vessel occlusion (LVO), are critical determinants of favorable outcomes. While Mobile Stroke Units (MSUs) – ambulances equipped with computed tomography (CT) imaging – have demonstrated efficacy in improving outcomes, their deployment is often constrained to urban environments due to cost-efficiency considerations. Blood biomarkers offer a potentially cost-effective alternative for stroke diagnosis and subtyping. Especially for patients with LVO, a prehospital biomarker-based identification could enable a streamlined transport strategy directly to thrombectomy-capable stroke centers. In this study, we evaluate the diagnostic accuracy and feasibility of a novel point-of-care test (POCT) in predicting LVO stroke, along with the levels of vascular biomarkers—NT-proBNP, D-Dimer, and H-FABP—from ultra-early whole-blood samples of patients with suspected stroke in a prehospital setting. The test integrates a blood-based multiplex lateral flow assay (LFA) with clinical decision support (CDS) software, accessible through a Mobile Application (App). The study was registered in the German Clinical Trials Register (DRKS-ID: DRKS00037840).Methods and analysisThis multicenter prospective observational study will include 800 patients with suspected stroke, enrolled within 24 h after symptom onset. Participants will be recruited at three Mobile Stroke Unit (MSU) sites in Berlin, Germany. Prehospital blood samples will be analyzed directly in the ambulance using the LVOCheck device. The test achieves its performance by quantifying the blood levels of the vascular biomarkers (NT-proBNP, D-Dimer, and H-FABP), and inputting these concentrations, along with neurological assessment score and patient-specific medical information such as age and blood pressure, to output predictive information on the probability of LVO stroke, together with all the input data. Additional clinical data, including final diagnoses, will be documented in electronic case report forms (eCRFs). The diagnostic performance of LVOCheck will be evaluated through comprehensive statistical analysis of the combined biomarker and clinical data, including assessment of sensitivity, specificity, and predictive models.DiscussionThis real-world study aims to evaluate the diagnostic accuracy and feasibility (including human factors and usability) of LVOCheck, a portable, non-invasive multiplex POCT at prehospital settings, such as an ambulance, in the prediction of acute LVO diagnosis and triage of suspected acute LVO stroke patients. Utilizing Mobile Stroke Units (MSUs) as recruiting sites enables the analysis of ultra-early biomarker levels from prehospital whole-blood samples combined with patient-specific medical information to provide a predictive risk of LVO stroke. A cost-effective and practical POCT could provide additional biochemical information to support prehospital LVO identification in the future, thereby potentially assisting emergency medical services in transport decisions regarding direct transfer to thrombectomy-capable centers. This may improve triage efficiency, treatment metrics and outcomes in both urban and rural settings.Clinical trial registrationhttps://www.drks.de/search/de/trial/DRKS00037840/details, Identifier DRKS00037840.